(untitled) (Fiep Bulletin - online, 2011)
The motor development is a process of learning and constant changes that happen on the motor behavior of the human being in a continuing and gradual way and it takes place during all lifetime. The objective of this present research was to investigate the motor profiles of 224 students, who practice physical education, 112 males and 112 females, from 7 to 8 years old, which represent 18% of students regularly enrolled at the state public schools of Macapá city. The method used to evaluate those skills was the protocol of tests of Rosa Neto’s (2002) Motor Development Scale (MDS), which evaluates the following elements of the motricity: fine motricity, global motricity, balance, corporal scheme, spatial organization, temporary organization and laterality. In face of data concerning the general motor ages (GMA) and the chronological age (CA), the general motor quotient was calculated and this facilitates the classification of the students tested in a MDS that goes from the upper superior to the very inferior, whose results were: 78% medium normal, 9% high normal, 9% low normal, 2% superior and 2% inferior. The results of t-test for dependent samples confirm the non-rejection of H0 hypothesis, that allows to conclude that at the usual significance level, there is no statistically significant difference between the GMA and CA for all the categories of students age and gender. These results make us infer that the students present similar characteristics in all elements of motricity, but when they are evaluated separately we noticed that some of these elements were accomplished with such degree of difficulty. We can conclude that the practice of these tasks can be made easy or difficult, according to the opportunities of the major motor experiences acquired through the well oriented practice, as well as the context in which they are inserted.